Memo to the new digital agenda commissioner - Reinhilde Veugelers; Bruno van Pottelsberghe de la Potterie (Bruegel, 2010)
Senior Resident Fellows Reinhilde Veugelers and Bruno van Pottelsberghe provide recommendations for the term of new Digital Agenda Commissioner Neelie Kroes in this supplement to Bruegel's Memos to the New Commission: Europe's Economic Priorities 2010-2015. They argue that Kroes should move past a focus on infrastructure and concentrate more on ICT's potential to contribute to growth in the European Union. This should include a focus on emerging ICT products and services to helpl foster an ICT single market and more public support for R&D and innovation, through tailored programmes designed to aid high-risk innovative projects conceived by new ICT companies.
Keywords: 330; Informationstechnik; Forschungs- und Technologiepolitik; Innovationspolitik; Telekommunikationspolitik; EU-Staaten